The Effect of Scout Extracurricular Activities in Mathematics Learning Outcomes on Students Class XI at Wahidiyah Senior High School - Hidayah, Anisha; Sari Indrayany, Eka (Universitas Islam Tribakti Lirboyo Kediri, 2023)
Extracurricular activities are activities outside of standard curriculum practice hours that are carried out to help to teach participants to improve their abilities according to their abilities and interests. Some problems arise at Wahidiyah Senior High School, students who are active in exploring non-academic activities such as Scout extracurricular activities often give up their academic needs in terms of learning outcomes. This research intends to identify the impact of extracurricular activities on the results of mathematics practice for students in class XI at Wahidiyah Senior High School. This research uses a quantitative approach with 2 variables namely scout extracurricular activities (), and students' practice results (). The population in this research is students of class XI for the academic year 2021 – 2022 at Wahidiyah Senior High School with a total of 198 students. The method of collecting data in this research was purposive sampling. Data was collected using questionnaires with Likert's ratios. Data analysis in this method experiments with a classic assumption experiment using a normality test, heteroscedasticity test, and autocorrelation test. The information analysis method in this research uses simple regression analysis, and experimental F analysis to respond to assumptions with the encouragement of IBM SPSS (Statistical Product and Service Solution) 25.0 for Windows. The results of the information analysis are as follows: (1) Extra-curricular activities affect the mathematics learning outcomes of students in class XI Wahidiyah Senior High School. Scout extracurricular activities can explain learning outcomes by 90% and the remaining 10% is explained by other variables that are not studied in this research